PAMERAN MEDIA PEMBELAJARAN MATEMATIKA: UPAYA MEMOTIVASI SISWA SD DALAM BELAJAR MATEMATIKA - M. Imamuddin; Afini Afridalia; Anisa Dwi Putri; Deffa Ryani Chairunnisa; Fazila Nawasyaira; Intan Pematasari Nurullulah; Nurazizah Paisal; Puja Qonita Sholihat; Sofi Yonalta (Universitas Pahlawan Tuanku Tambusai, 2023)
Student motivation is an intrinsic factor within students that is able to influence students in their learning. This motivational factor can also affect student achievement. This PKM Community Service activity aims to increase or arouse students' motivation to learn mathematics by carrying out exhibition activities for students' mathematics learning media. The PKM Mandiri location is located at SDN 05 Kubang Putih Agam which will be held on December 3, 2022 which will be attended by students of grades IV, V, and VI. The results of the Mandiri PKM activities, namely the mathematics learning media exhibition which was held were very creative, interesting, and fun. While the benefits of helping students in making it easier to understand the material or mathematical concepts. Besides that, it is able to arouse students' motivation to learn mathematics. Keywords: PKM, Mathematics Learning Media Exhibition, Learning Motivation